Managing Intangible Assets In Innovation Based Competition Era - Meily Margaretha .; Lina Anatan . (Universitas Kristen Maranatha, 2009)
This paper reviews the role of intangible assets as source of competitive advantage and how to manage their assets in innovation based competition era. Innovation based competition has radical consequences on organizational management practices; in other word innovation has become ever more central to firms competitiveness. In today's business competition, organizations are highlighting the importance of intangible assets as source of competitive advantage. It is represent significant values drivers for organization such as human capital, customer capital, information database, software, brand, patent, and business processes. In other the balance the investment between physical and intangible assets, organization have to able to identify and to calculate the value of their intangible assets. One way to manage intangible assets is through knowledge management. And the most important factor to be considered is aligning the organization intangible assets management strategy with its vision, values, organization strategy and culture, so that management will be able to reap the reward from its most valuable assets.Keywords: intangible assets, innovation-based competition, intangible asset management framework, competitive advantage.